Analisis Pengaruh Kualitas Pelayanan dan Kualitas Produk terhadap Kepuasan Pelanggan pada Rumah Makan Nasi Liwet Cipancar - Abdurohman, Abdurohman; Adji, Widwi Handari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
service and product quality on consumer satisfaction at Nasi Liwet Cipancar Restaurant. As many as 99 respondents for the sample taken using the Non-Probability sampling technique with the Accidential sampling approach. So that there is a simultaneous influence between variable X1 and variable X2 on Y with SPSS V.26 of 56% and the remaining 43.4% is attributed to other factors that were not examined in this research. Keywords: Service Quality, Product Quality, Customer Satisfaction